Euthanasia As A Virtuous And Rightful Act - Sharma, Bharti; Thareja, Shivi (Trinity Law Review, 2021)
"I’m 29 years old and I’ve chosen to be voluntarily euthanised. I’ve chosen this because I have a lot of mental health issues. I suffer unbearably and hopelessly. Every breath I take is torture…" These were the lines said by Aurelia Brouwers, a 29-year-old Dutch woman, when asked that why she wants to embrace death. Evidently, it sounds devastating and reflects the misery and agony that this woman underwent. She was euthanised on 26 January 2018. She drank the poison supplied by a doctor and was lay down to die. Euthanasia is illegal in most countries, but in the Netherland, it is allowed, if a doctor is convinced that a patient’s suffering is "unbearable with no prospect of improvement" and if there is "no reasonable alternative in the patient’s situation". Aurelia Brouwers’ wish to die came with a long history of mental illness. When she was 12, she suffered from depression and was later diagnosed with Border Line Personality Disorder. She was chronically depressed and sicidal, had anxiety, psychoses and heard voices. During the last fortnight of her life, Aurelia was often distressed and had self-harm. One of the journalists, who documented the last days of her life, recalls that it was quite obvious that she was under constant mental pressure and didn’t talk much on any other thing apart from euthanasia. On that, she was crystal-clear. She expressed, "I’m stuck in my own body, my own head, and I just want to be free. I have never been happy - I don’t know the concept of happiness."